2019
DOI: 10.1371/journal.pone.0214349
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enalapril and paricalcitol treatment on diabetic nephropathy and renal expressions of TNF-α, p53, caspase-3 and Bcl-2 in STZ-induced diabetic rats

Abstract: This study aimed to assess the renopreventive effect of enalapril and/or paricalcitol on streptozotocin (STZ) diabetes-induced nephropathy and to elucidate their mechanisms of action through investigation of the effects on renal oxidative stress, antioxidant defense system and expressions of TNF-α, p53, caspase-3, and Bcl-2. Diabetes mellitus was induced in fasting male Wistar rats by single intraperitoneal injection of STZ (45 mg /kg b.w.) dissolved in citrate buffer (pH 4.5). Ten days after STZ injection, th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 63 publications
6
36
0
Order By: Relevance
“…Diabetes mellitus is often associated with alterations of kidney and liver functions in rats; therefore, we studied the impact of TTA-DFP-nCOF/insulin on these vital functions. 99 Fig. 3g shows the histopathological study of the liver and kidney to detect organ pathology in non-diabetic rats and S.C. insulin- and TTA-DFP-nCOF/insulin-treated rats.…”
Section: Resultsmentioning
confidence: 99%
“…Diabetes mellitus is often associated with alterations of kidney and liver functions in rats; therefore, we studied the impact of TTA-DFP-nCOF/insulin on these vital functions. 99 Fig. 3g shows the histopathological study of the liver and kidney to detect organ pathology in non-diabetic rats and S.C. insulin- and TTA-DFP-nCOF/insulin-treated rats.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth mentioning that p53, Bax and Bak as well as Bcl-2 are implicated in the intrinsic pathway of apoptosis that is activated by ROS produced by mitochondria ( Figure 25 and Figure S25 ). The tumor suppressor p53 is a transcription factor that is activated upon DNA damage to induce target genes involved in either cell growth arrest or apoptosis [ 129 , 130 , 131 ]. The p53, Bax and Bak mediate intrinsic signaling pathway to activate caspase-9 that in turn activate caspase-3 leading to apoptosis ( Figure 25 and Figure S25 ) [ 132 ].…”
Section: Discussionmentioning
confidence: 99%
“…The p53, Bax and Bak mediate intrinsic signaling pathway to activate caspase-9 that in turn activate caspase-3 leading to apoptosis ( Figure 25 and Figure S25 ) [ 132 ]. This activation can be controlled by the Bcl-2, which has anti-apoptotic effects [ 130 , 131 , 132 , 133 ]. Otherwise, TNF-α activates the extrinsic pathway of apoptosis by its binding to TNF receptor (TNFR) and death receptor ( Figure 25 and Figure S25 ).…”
Section: Discussionmentioning
confidence: 99%
“…They increase risks for nephropathy and cardiovascular diseases (Braunwald, 2019). Many studies have indicated that DM is associated with excess production of reactive oxygen species (ROS) (Peerapatdit et al., 2006; Ahmed, et al., 2017; Ahmed, et al., 2019; Ahmed, et al., 2017; Saravanan & Ponmurugan, 2011), which in turn, is implicated in the pathogenesis of many diabetic complications including atherosclerosis, kidney injury and heart failure (Wilcox & Gutterman, 2005). The production of ROS is reduced by an antioxidant defense system which included both non‐enzymatic antioxidants including vitamin C, vitamin D and glutathione (GSH) and ROS‐scavenging antioxidant enzymes such as catalase (CAT), GSH peroxidase (GPx), GSH‐S‐transferase (GST) and superoxide dismutase (SOD) (Adewole et al., 2008; Budin et al., 2009; Tan et al., 2018).…”
Section: Introductionmentioning
confidence: 99%